2020
DOI: 10.1016/j.adro.2019.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Interinstitutional Plan Quality Assessment of 2 Linac-Based, Single-Isocenter, Multiple Metastasis Radiosurgery Techniques

Abstract: Purpose: Interest and application of stereotactic radiosurgery for multiple brain metastases continue to increase. Various planning systems are available for linear accelerator (linac)ebased single-isocenter multiple metastasis radiosurgery. Two of the most advanced systems are BrainLAB Multiple Metastases Elements (MME), a dynamic conformal arc (DCA) approach, and Varian RapidArc (RA), a volumetric modulated arc therapy (VMAT) approach. In this work, we systematically compared plan quality between the 2 techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 29 publications
5
27
1
Order By: Relevance
“…Median conformity index and gradient index, which are commonly used to describe SRS quality planning, were 1.32 and 3.94, respectively, consistent with those reported in other published studies using either DCA or VMAT techniques. 8 , 9 , 10 , 11 , 12 , 13 , 28 , 29 , 30 In a comparative study of SIMT DCA and VMAT SRS plans generated by the commercially available automated planning software Multiple Brain Metastases (Brainlab) and HyperArc (Varian), respectively, Ruggeri et al 29 observed comparable high plan quality in 20 patients with 2 to 10 BM, although the conformity index was slightly better for VMAT plans. In another study comparing SIMT DCA to VMAT SRS plans in 30 patients with 4 to 10 BM, Liu et al 30 showed that the VMAT technique resulted in better conformity and V12Gy-8Gy volumes; in contrast, other studies suggest that DCA plans perform better than VMAT in terms of healthy brain sparing and treatment efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Median conformity index and gradient index, which are commonly used to describe SRS quality planning, were 1.32 and 3.94, respectively, consistent with those reported in other published studies using either DCA or VMAT techniques. 8 , 9 , 10 , 11 , 12 , 13 , 28 , 29 , 30 In a comparative study of SIMT DCA and VMAT SRS plans generated by the commercially available automated planning software Multiple Brain Metastases (Brainlab) and HyperArc (Varian), respectively, Ruggeri et al 29 observed comparable high plan quality in 20 patients with 2 to 10 BM, although the conformity index was slightly better for VMAT plans. In another study comparing SIMT DCA to VMAT SRS plans in 30 patients with 4 to 10 BM, Liu et al 30 showed that the VMAT technique resulted in better conformity and V12Gy-8Gy volumes; in contrast, other studies suggest that DCA plans perform better than VMAT in terms of healthy brain sparing and treatment efficiency.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 , 10 , 11 , 12 , 13 , 28 , 29 , 30 In a comparative study of SIMT DCA and VMAT SRS plans generated by the commercially available automated planning software Multiple Brain Metastases (Brainlab) and HyperArc (Varian), respectively, Ruggeri et al 29 observed comparable high plan quality in 20 patients with 2 to 10 BM, although the conformity index was slightly better for VMAT plans. In another study comparing SIMT DCA to VMAT SRS plans in 30 patients with 4 to 10 BM, Liu et al 30 showed that the VMAT technique resulted in better conformity and V12Gy-8Gy volumes; in contrast, other studies suggest that DCA plans perform better than VMAT in terms of healthy brain sparing and treatment efficiency. 13 , 28 Although such indexes remain of interest to assess the dosimetric quality of treatment plans, the correlation between planning quality and clinical outcomes remains to be clarified, 31 and the superiority of one technique over another in terms of plan quality metrics is unsustained.…”
Section: Discussionmentioning
confidence: 99%
“…The phantom setups, prescribed doses, plane override distances, and gamma pass-rates are listed in Table II. The software successfully computed all geometric phantom setups and was able to accurately extract the relevant dose plane for each measurement geometry at the chosen planar resolution of 0.5 9 0.5 mm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…This approach can significantly spare the dose to normal brain tissue while simultaneously delivering a therapeutic dose to a multitude of target volumes. 2 This delivery technique is in contrast to the more classical practice of treating a limited number of targets (<3-4) by placing each target sequentially to the machine isocenter. Indeed, in most cases treatment plans utilizing a mono-isocentric approach will have no target present at the isocenter of the machine during treatment delivery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation